A case of juvenile chronic myeloid leukemia with XX/XXX mosaicism - Yeşilipek, M. Akif; Lüleci, Güven; Oygür, Nihal; Berker, Sibel; Yegin, Olcay (The Turkish Journal of Pediatrics, 1992)
Cytogenetic abnormalities are rarely found in patients with juvenile chronic myelogenous leukemia (JCML). In patients with chromosomal abnormalities, chromosomes 7 and 8 are usually involved. A case of JCML with 47 XXX and a 46 XX karyotype is described and the literature is reviewed. To our knowledge, this is the first case ever to have been reported.
Keywords: juvenile chronic myeloid leukemia; chromosome; XXX karyotype